ANALISA USAHA LAUNDRY (HOOP LAUNDRY) DI KOTA MATARAM DENGAN METODE BREAK EVEN POINT (BEP) - Wijana, Made; Wirya A., I.G.A.K. Chatur Adhi; Boli, B.V.S. (Energy, Materials and Product Design, 2023)
Laundry is a business in the field of clothes washing services where dirty clothes are processed until clean and ready to distributed, this business is very promising because of the high level of demand for this service. Therefore, business actors in this field, namely Hoop Laundry, to continue to develop, must be supported by maximum profits by doing profit planning to find out whether this business is profitable or not.To plan profit, a tool is needed, one of which is the determination of the break- even point. In profit planning, break even point analysis is a profit planning approach that is based on the relationship between costs and income.The results of this study, it is known that the average number of kg of laundry per month produced is 1,702.52 kg with a Fixed Cost (FC) of Rp. 25,510,500 and Variable Cost (VC) of Rp. 61,828,852.5. From the laundry price per kg (p) which is IDR 6,000 the number of kg of laundry produced to reach the Break Even Point (BEP) condition is12,984 kg of laundry with a time of 7.6 months where the total expenses (TC) are equal to the total income (TR) which is IDR 77,902,498